2019
DOI: 10.1088/1755-1315/330/5/052029
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Development Strategy of Rural Logistics in China Post

Abstract: Through the analysis of the current situation of rural logistics development, we find that there are many problems in the development of rural logistics in China: imperfect infrastructure, incomplete use of information systems, the development of rural logistics can not be connected with the city, and the logistics system of rural development is chaotic; through the analysis, we find that China Post has a very strong advantage in rural logistics, according to economic development. The exhibition situation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Solving the last mile delivery problem in rural areas with multimodal transport has gradually become a hot research topic. Chen et al [41] found that China Post has a very strong advantage in rural logistics, and multimodal transport could improve the service quality of last mile delivery. Gong proposed integrated urban-rural logistical systems, including material flow, financing flow, information flow, and commerce flow, which has become an effective way to break through the division between urban and rural logistics and realize their coordinated development [42].…”
Section: Introductionmentioning
confidence: 99%
“…Solving the last mile delivery problem in rural areas with multimodal transport has gradually become a hot research topic. Chen et al [41] found that China Post has a very strong advantage in rural logistics, and multimodal transport could improve the service quality of last mile delivery. Gong proposed integrated urban-rural logistical systems, including material flow, financing flow, information flow, and commerce flow, which has become an effective way to break through the division between urban and rural logistics and realize their coordinated development [42].…”
Section: Introductionmentioning
confidence: 99%